Can large-scale tree cover change negate climate change impacts on future water availability? - F. Engel; A. J. Hoek van Dijke; C. T. J. Roebroek; C. T. J. Roebroek; C. T. J. Roebroek; I. Benedict (Hydrology and Earth System Sciences)
The availability of fresh water over land may become increasingly scarce under climate change (CC), and natural and human-induced tree cover changes can further enhance or negate the water scarcity. Previous studies showed that global tree cover change can have large impacts on water availability under current climate conditions, but they did not touch upon the implications of global tree cover change under climate change. Here, we study the hydrological impacts of large-scale tree cover change (climate-induced changes in combination with large-scale afforestation) in a future climate (SSP3-7.0) following an interdisciplinary approach. By combining data from five Coupled Model Intercomparison Project phase 6 (CMIP6) climate models with a future potential tree cover dataset, six Budyko models, and the UTrack moisture recycling dataset, we can disentangle the impacts of climate change and future tree cover change on evapotranspiration, precipitation, and runoff. We quantify per grid cell and for five selected river basins (Yukon, Mississippi, Amazon, Danube, and Murray–Darling) if tree cover changes can enhance or counteract the climate-driven changes in runoff due to their impact on evapotranspiration and moisture recycling. Globally averaged, the impacts of climate change and large-scale tree cover change on runoff can be of similar magnitude with opposite signs. While climate change may increase global runoff, we estimate that tree cover change could reverse this effect, which may result in a limited net impact on global runoff relative to the present climate and current tree cover. Nevertheless, the local changes in runoff due to tree cover change and climate change can be substantial, with increases and decreases of more than 100 mm yr−1. We show that, for approximately 16 % of the land surface, tree cover change can increase the water availability significantly. However, for 14 % of the land surface, both tree cover change and climate change could decrease water availability by more than 5 mm yr−1. For each of the selected catchments, the direction and magnitude of the impacts of climate change and tree cover change can vary, with dominating climate change impacts in all basins except the Mississippi River basin. Our results show that ecosystem restoration projects targeting an altered tree cover should consider the corresponding hydrological impacts to limit unwanted (non-)local reductions in water availability.